Ipo Information Disclosure And Price Stabilisation Action From The Perspective Of Information Asymmetry In Hong Kong Listed Companies - Xu, Morong (2024)
The topics of IPO have attracted attentions from scholars for a long time. Among these research topics, price stabilisation, which is an aftermarket action taken by underwriters, is relatively less concentrated by prior studies. Factors which cause the stabilisation done by underwriters are not clear, owing to the barrier resulted from the non-mandatory disclosure of such actions in many countries. Meanwhile, as a compulsory document for IPO issuers, the prospectus contains sufficient information for investors to make decision for IPO investment. Recent studies have focused on the information disclosed in IPO prospectus, such as the text content and textual tone, and its corresponding influence on market performance. Yet, studies which have investigated the relationship between the information disclosure of IPO prospectus and price stabilisation are scarce. This thesis probes into the potential factors of price stabilisation from the theoretical perspective of information asymmetry by examining how the information disclosed in the IPO prospectus can impact the aftermarket stabilising actions using a sample data from 2004 to 2021 in Hong Kong stock market. Specifically, the effects of the information disclosure related to cornerstone investors, Chinese state ownership, as well as the narrative uncertainty contained in the prospectus, are investigated using ordinary least square regression model. This thesis finds that the information related to cornerstone investors is positively correlated with price stabilising actions in the aftermarket. The information relevant to Chinese state ownership is statistically negatively associated with price stabilisation.